2016
DOI: 10.1111/oik.03404
|View full text |Cite
|
Sign up to set email alerts
|

Pyramids of species richness: the determinants and distribution of species diversity across trophic levels

Abstract: How species richness is distributed across trophic levels determines several dimensions of ecosystem functioning, including herbivory, predation, and decomposition rates. We perform a meta-analysis of 72 large published food webs to investigate their trophic diversity structure and possible endogenous, exogenous, and methodological causal variables. Consistent with classic theory, we found that published food webs can generally be described as 'pyramids of species richness'. The food webs were more predator-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…Relationships within a community, energy flow, and linkages between biota and the environment are all encompassed in Lindeman's approach. The idea of energy flow in an ecosystem strengthened earlier studies such as biomass pyramids (Elton, 1927;Turney and Buddle, 2016), opening the way for incorporation of food webs into ecology to understand ecosystem processes (McIntosh, 1986;Sale, 2002). Definition of ecosystem processes is crucial to trophodynamic studies because they encompass biological, physical, and chemical mechanisms that link species and facilitate energy flow.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Relationships within a community, energy flow, and linkages between biota and the environment are all encompassed in Lindeman's approach. The idea of energy flow in an ecosystem strengthened earlier studies such as biomass pyramids (Elton, 1927;Turney and Buddle, 2016), opening the way for incorporation of food webs into ecology to understand ecosystem processes (McIntosh, 1986;Sale, 2002). Definition of ecosystem processes is crucial to trophodynamic studies because they encompass biological, physical, and chemical mechanisms that link species and facilitate energy flow.…”
Section: Introductionmentioning
confidence: 77%
“…Mesopredators are considered to have less of an effect on the trophic structure of a system (Paine, 1980;Estes et al, 2011), but there is little empirical evidence to support this due to difficulty in defining predator-prey relationships. A recent meta-analysis of food web studies found that aquatic models produced a strong pyramid pattern, suggesting scale variance in predator-prey ratios according to biomass power laws consistent with Hatton et al (2015) (Turney and Buddle, 2016). The analysis also showed that on average aquatic communities have a higher diversity of mesopredator species than herbivores, with low abundance of top predators.…”
Section: Controlling Forces In Trophodynamicsmentioning
confidence: 84%
See 3 more Smart Citations